2006
DOI: 10.1080/07315724.2006.10719522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight, Body Composition and Resting Metabolic Rate (RMR) in First-Year University Freshmen Students

Abstract: The present study supports the notion that freshmen students, on average, gain weight during their first semester; however, this weight gain may be more modest than generally perceived. The study also provides important new data on changes in diet, body composition and RMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 8 publications
8
43
1
2
Order By: Relevance
“…These papers showed the first semester of the first year at university was a critical time for weight gain 31,37,44 ; an average gain of 1.5kg was gained over the first 3-4 months 31, 37, 44 ), with only slightly higher rates seen at the end of the academic year (1.9kg over nine months 29,39,42 ). However, little or no weight was gained in the subsequent years of study 40 .…”
Section: Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…These papers showed the first semester of the first year at university was a critical time for weight gain 31,37,44 ; an average gain of 1.5kg was gained over the first 3-4 months 31, 37, 44 ), with only slightly higher rates seen at the end of the academic year (1.9kg over nine months 29,39,42 ). However, little or no weight was gained in the subsequent years of study 40 .…”
Section: Activitymentioning
confidence: 99%
“…This paper reported the results of three trials conducted in the US and Europe, two of which were carried out for a year and the third for three years. The combined trials, which observed more than 2,300 women (aged [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], reported modest weight gain (<2.3kg at 12 months) with large individual variation 53 .…”
Section: Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent research suggests that the average amount of weight gained by first-year college students-the so-called "Freshman 15"-is more likely to be around 2.5 to 6 pounds, others have argued that college freshmen gain weight at a greater rate than do others in the general population, and behaviors at this age likely influence long-term behaviors 14,15,16,17,18,19,20,21,22,23 . In fact, the Healthy People 2010 program urges policymakers to seize the "window of opportunity" to encourage children and young adults to establish good eating and exercise behaviors now so that they might carry over into adulthood 24 , whereas college campuses have been identified as a particularly important target for weight-related policy interventions 25 .…”
mentioning
confidence: 99%
“…A strategy for prevention of obesity is to identify critical periods of weight gain in the human life cycle (1). It seems that weight gain occurs during the first year of college (2). Weight gain and lifestyle changes in this period may contribute to obesity in the adulthood period (3).…”
Section: Introductionmentioning
confidence: 99%